2017
DOI: 10.1038/srep41552
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PDGFR signaling prevents muscular fatty infiltration after rotator cuff tear in mice

Abstract: Fatty infiltration in muscle is often observed in patients with sizable rotator cuff tear (RCT) and is thought to be an irreversible event that significantly compromises muscle plasticity and contraction strength. These changes in the mechanical properties of the affected muscle render surgical repair of RCT highly formidable. Therefore, it is important to learn more about the pathology of fatty infiltration to prevent this undesired condition. In the present study, we aimed to generate a mouse model that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 39 publications
(52 reference statements)
2
40
0
Order By: Relevance
“…16,26 We have shown that FAPs are induced in the supraspinatus (SSP) muscle after RCT and that fatty infiltration can be suppressed by targeting these cells through platelet-derived growth factor receptor (PDGFR) activity inhibition in mice. 22 Because the biological characteristics of FAPs are nearly identical between humans and mice, 23 our observations indicate that FAPs are, at least, one of the major sources of adipocytes responsible for muscle fatty infiltration after RCT in humans.…”
mentioning
confidence: 81%
“…16,26 We have shown that FAPs are induced in the supraspinatus (SSP) muscle after RCT and that fatty infiltration can be suppressed by targeting these cells through platelet-derived growth factor receptor (PDGFR) activity inhibition in mice. 22 Because the biological characteristics of FAPs are nearly identical between humans and mice, 23 our observations indicate that FAPs are, at least, one of the major sources of adipocytes responsible for muscle fatty infiltration after RCT in humans.…”
mentioning
confidence: 81%
“…Experimental RC tears in rats and mice involving the transection of supraspinatus and infraspinatus tendons (TT) along with the suprascapular nerve (DN) have replicated the marked degenerative fibrosis and fat accumulation found in these patients. [11][12][13] The rodent model of massive RC tears has been used by researchers to study the pathological progression of the disease and to improve their understanding of the cellular response [13][14][15] to injury, the molecular pathways that are responsible for it [16][17][18] and test therapeutic approaches to attenuate the progression of muscle degeneration. [19][20][21][22][23] One of the most commonly used assays for analysis of development of damage in injured RC is muscle histology.…”
Section: Introductionmentioning
confidence: 99%
“…23 Current therapies to improve functional outcomes after massive rotator cuff tears (RCTs) focus on tendon-to-bone healing but show limited success. 32,44,58 New strategies are focused on decreasing or reversing muscle atrophy, fibrosis, or FI, 18,26,49 but it is unclear if these changes contribute equally or even codependently to RC muscle function.…”
mentioning
confidence: 99%